Precipitation of Trichoderma reesei commercial cellulase preparations under standard enzymatic hydrolysis conditions for lignocelluloses - Chylenski, Piotr (2012)
Comparative studies between commercial Trichoderma reesei cellulase preparations show that, depending on the preparation and loading, total protein precipitation can be as high as 30 % under standard hydrolysis conditions used for lignocellulosic materials. ATR-IR and SDS-PAGE data verify precipitates are protein-based and contain key cell wall hydrolyzing enzymes. Precipitation increased considerably with incubation temperature; roughly 50–150 % increase from 40 to 50 °C and 800 % greater at 60 °C. All of the reported protein losses translated into significant, and often drastic, losses in activity on related 4-nitrophenyl substrates. In addition, supplementation with the non-ionic surfactant PEG 6,000 decreased precipitation up to 80 % in 24 h precipitation levels. Protein precipitation is potentially substantial during enzymatic hydrolysis of lignocelluloses and should be accounted for during lignocellulose conversion process design, particularly when enzyme recycling is considered.